Volume 2: Combustion, Fuels and Emissions, Parts a and B 2011
DOI: 10.1115/gt2011-46256
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of NOx Emission of a Lean Staged Combustor for an Aircraft Engine

Abstract: Due to the increasing demands for environment protection, the regulation of NOx emissions from aircraft engines specified by ICAO have become more stringent year by year. A combustor with lean staged fuel injectors is one of the effective methods to reduce NOx emissions. Kawasaki heavy industries Ltd GTBC and Japan Aerospace Exploration Agency (JAXA) have been conducting joint research on a lean staged concentric fuel nozzle for a high pressure ratio aero engine. High pressure combustion tests were performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Because of the possibility of controlling NO x emissions at a very low level, the lean premixed staged combustion is often applied by most manufacturers to replace the traditional diffusion combustion. 3,4 The lean premixed combustor developed by Rolls-Royce, 57 General Electric 8,9 and JAXA 1012 have been widely used to meet the requirements of low emission. The fuel and the oxidant are premixed first when lean premixed combustion technology is adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the possibility of controlling NO x emissions at a very low level, the lean premixed staged combustion is often applied by most manufacturers to replace the traditional diffusion combustion. 3,4 The lean premixed combustor developed by Rolls-Royce, 57 General Electric 8,9 and JAXA 1012 have been widely used to meet the requirements of low emission. The fuel and the oxidant are premixed first when lean premixed combustion technology is adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Then the two injectors had been tested on realistic altitude relight conditions, which demonstrated comparable altitude relight characteristics. 13 Kobayashi et al 14,15 developed a lean staged combustor, which selected prefilm atomizer as the pilot fuel nozzle. The key design parameters of this injector were experimentally examined on ignition stability, and results indicated that concentrated fuel distribution in the central recirculation zone was beneficial for the flame stability.…”
Section: Introductionmentioning
confidence: 99%
“…For reduction of NOx from aircrafts, coaxial-staging lean burn fuel injection systems have been studied intensively these days [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and some of them have been already in service. Typically, they consist of a non-premixedmode pilot nozzle at the center for flame stability and a lean premixed-mode main nozzle surrounding the pilot for drastic NOx reductions.…”
Section: Introductionmentioning
confidence: 99%